How to Improve the Science and Engineering Education in Islamic Countries? - Zekai Şen (Üniversite Araştırmaları Dergisi)
The evolutions of science, education and especially engineering training had different trends stating from the very root of human history. The future improvements in scientific and engineering education require extensive literature review to assess objectively the contributions of different civilizations among which Islamic education system had a unique feature in the past towards the researches in astronomy, physics, chemistry, algebra, robotics, medicine, etc. The universities are the highest educational institutions which provide every nation with enlightened individuals; promote intellectual development; advent and promote innovations and discoveries in field and laboratory. Prior to all these activities, it is necessary that the same universities should produce philosophical schools of thought, literature, artistic and social trends. Researchers should be able to put forward theories of good, right and beauty with ideas and orientations that serve as a reference for future policy makers in different sectors for the prosperity of the nation and humanity in general. After long centuries of slackness, the higher education is gaining momentum in the Muslim World which is striving to effect comprehensive developments in the present century. Almost in every aspects of life highly-trained manpower are required. Unfortunately, scientific philosophical thinking and logical refinement of scientific information aspects are missing in almost all the universities in Muslim countries. Especially, three T-principle as Takhayyul (imagination), Tasawwur (design, geometrical shape description) and Tafakkur (idea generation) do exist very rarely in our universities. In fact, the 3-T principle is the trigger of scientific information generation process. This paper elaborates on the education systems during the past Islamic periods, which ignited the educational system development in the western countries; its decline; and the present situation with ever increasing momentum towards the future. It is emphasized that the higher education and scientific research should have philosophy, logic, geometry and natural event visualizations prior to mathematical and computational calculations in engineering education.